IT TOOLS OF SOCCER PERFORMANCE ANALYSIS - Karikás, Krisztián; Ráthonyi, Gergely (Stadium - Hungarian Journal of Sport Sciences, 2020)
Soccer is the world's most popular sport, well represented by the fact that the 2018 Russian Soccer World Cup has been followed by more than half of the world's population on some platform. For each win, teams do their best to create a competitive advantage over their rivals. Information technology is one of the explosive fields that has led to significant changes in soccer as well. For example, innovative solutions have emerged in the sports industry that have contributed to the acceleration of the game, technological innovations in soccer streaming can enhance the fan experience with up to 3-dimensional replays, or recently introduced video referee and goal line technology to solve disputed situations. In soccer, the analysis of the match and the resulting data that characterizes the performance of the players and the team, which can be analyzed from many angles: technical, tactical, mental and physiological, can play an important role. The advancement of technology has made it possible for soccer professionals to access significant amounts of variable format data, the processing and utilization of which is crucial to them.The primary objective of this article is to present the importance of IT tools of performance analysis in soccer.